2003
DOI: 10.1634/stemcells.21-6-654
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length in Subpopulations of Human Hematopoietic Cells

Abstract: CD38-cells could not be observed. We conclude that the telomere length in subpopulations of hematopoietic cells does appear to be correlated with the known proliferative potential of such cells and that further characterization of cells on the basis of telomere length is warranted for enrichment of very rare precursors of hematopoietic and other tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 30 publications
1
35
0
1
Order By: Relevance
“…From P3 to P9 there were Ϸ18 PDs with an average telomeric shortening of 130 bp per PD. This rate of telomere attrition is comparable with that of human bone marrow stem cells (9). Additionally, nearly 50% of the telomerase activity in hCSCs at P3-P4 was still present at P8-P9 (Fig.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…From P3 to P9 there were Ϸ18 PDs with an average telomeric shortening of 130 bp per PD. This rate of telomere attrition is comparable with that of human bone marrow stem cells (9). Additionally, nearly 50% of the telomerase activity in hCSCs at P3-P4 was still present at P8-P9 (Fig.…”
Section: Resultssupporting
confidence: 74%
“…Critical telomere length associated with growth arrest and cellular senescence of hCSCs and human hematopoietic SCs varies from 2.0 to 1.5 kbp (3,9). The fraction of hCSCs with critical telomeric shortening increased from 1% at P3-P4 to 2% at P5-P6 and 5% at P8-P9.…”
Section: Resultsmentioning
confidence: 99%
“…The use of hematopoietic cells as a proxy for average individual telomere length is complicated by the variation in telomere length observed within leukocyte subsets (42), as well as quantifiable changes in subset populations observed to occur with aging (43). Selection of a specific leukocyte subset, for example lymphocytes, would eliminate cell-to-cell variation and theoretically provide a more constant measure, although there is evidence that whole-blood telomere length Cancer Epidemiology, Biomarkers & Preventioncorrelates well with the mononuclear population (44).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this assumption, analysis of human HSC sub-populations revealed a decline in telomere length from immature CD34 þ 38À to more committed CD34 þ 38 þ cells. 58 As PB myeloid cells are characterized by a relatively short lifespan, one could hypothesize that, at any point of time, the telomere length in these cells reflects the telomere length of the HSC they are derived from. Indeed, comparative analysis revealed that telomere length in bone marrow aspirates as compared to peripheral blood leukocytes (PBLs) and mononuclear cells (MNCs) as well as in CD34 þ cells compared to PBSC harvests was shown to be closely correlated.…”
Section: Telomeres and Stem Cell Turnover In Normal Hematopoiesismentioning
confidence: 99%